Social Returns to Education : Evidence From Italian Local Labor Market Areas - Dalmazzo, A.; De Blasio, Guido (Washington, D.C. : International Monetary Fund, 2003)
The paper provides a quantitative assessment of social returns to education in Italy. It shows that, after controlling for individual characteristics, local average human capital is positively correlated with individual wages, with estimated social returns between 2 and 3 percent. This result is robust to alternative estimation methods and does not seem to depend on endogenous sorting. The paper also shows that social returns are higher in the lagged areas of the south of Italy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet